2019
DOI: 10.2147/oajsm.s161485
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical utility of tensiomyography for muscle function analysis in athletes</p>

Abstract: An exhaustive review has been made to filter the studies that have analyzed muscle function though tensiomyography (TMG) with elite or well-trained athletes. The results of this review indicate that the several protocols used in athletes to find the displacement-time curve with greater maximum radial muscle displacement showed a good-excellent reliability. TMG has been used to characterize athletes’ muscles contractile properties from specific sports disciplines, although there are very few sports that have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…The TMG have been recently used to evaluate fatigue-induced muscle changes 43,44 , to assess muscle impairments 45 , to evaluate and quantify painful muscle trigger points 46 and to corroborate rehabilitation muscle adaptations along the time 47 in specific populations. These studies showed the TMG as a really clinical useful tool to evaluate muscle characteristics and changes but, due to the specificity of the population, it is not possible to compare them with data from this study 48 . No studies showing normative data for healthy and active young adults were found.…”
Section: Discussionmentioning
confidence: 85%
“…The TMG have been recently used to evaluate fatigue-induced muscle changes 43,44 , to assess muscle impairments 45 , to evaluate and quantify painful muscle trigger points 46 and to corroborate rehabilitation muscle adaptations along the time 47 in specific populations. These studies showed the TMG as a really clinical useful tool to evaluate muscle characteristics and changes but, due to the specificity of the population, it is not possible to compare them with data from this study 48 . No studies showing normative data for healthy and active young adults were found.…”
Section: Discussionmentioning
confidence: 85%
“…Dm and Tc measurements were made using a specific electrical stimulator (TMG-S2) and TMG-OK 3.0 software as well as a displacement sensor set at 0.17 N·m −1 (TMG-BMC, Ljubljana, Slovenia), which was placed perpendicular to the muscle belly. Available information suggests that TMG is a valid method for muscle assessment that is useful both clinically and in sports for monitoring muscle fatigue and recovery [ 15 , 22 ]. Mechanical properties under submaximal (40 mA) and individual maximal conditions were obtained after a single electrical stimuli (1 ms).…”
Section: Methodsmentioning
confidence: 99%
“…In order to objectively evaluate the effect of these therapies on the recovery of athletes (both acute and chronic), the application of technologies to assess the condition of muscle tissue is required, to choose the application of one particular technique over another. Muscle assessment by tensiomyography (TMG) enables the non-invasive analysis of several parameters associated with neuromuscular fatigue/recovery, including radial displacement (Dm), which is related to muscle stiffness [ 15 ], and contraction time (Tc), which is the time that elapses between 10% and 90% of muscle displacement and varies depending on the type of muscle fiber and degree of fatigue [ 16 ]. Based on these considerations, the aim of this study was to evaluate the effect of different recovery treatments (MT, MV, PT and FR) on the contractile properties of skeletal muscle through TMG (Tc and Dm), after performing an eccentric overload training session.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used TMG as an injury prevention tool for the detection of muscle group imbalances and side-to-side asymmetries (García-García et al, 2019;Sánchez-Sánchez et al, 2018). It is also used to measure contractile properties (Dahmane et al, 2001;Đorđević et al, 2011) and mechanical responses based on radial muscle belly displacement (Tous-Fajardo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%